The effect of mobile messaging-based health interventions on non-communicable disease health risks and behaviours - Emeran, Aminah (Department of Human Biology, 2025)
Introduction: The prevalence of non-communicable diseases (NCDs) has increased rapidly, with NCDs being a leading cause of death globally. Despite the high mortality rate, NCDs are preventable and can be managed through addressing modifiable risk factors such as obesity and physical inactivity. Many public health interventions have aimed to reduce NCD risk factors, through supporting various lifestyle modifications. These interventions include Mobile Health (mHealth) interventions, which involve the use of mobile technology to provide health care and support to patients remotely. Community-based programmes may benefit from the use of mHealth interventions, due to the potential of these interventions for scalability and cost effectiveness. Aim: The aim of this thesis was to develop, implement and evaluate a pilot mHealth intervention that delivered automated, one-way WhatsApp messages for the promotion of healthy behaviour changes, as part of a pre-existing community health programme, Western Cape on Wellness (WoW!). Prior to the implementation of the pilot intervention, formative research was conducted, which included i) performing a systematic review and meta-analysis to better understand existing mHealth literature relevant to the pilot study, and ii) conducting a prospective descriptive study that aimed to determine the baseline health status, health goals, and health barriers of the population in which the intervention would be piloted. Methods: A mixed method approach was used. First a systematic review and meta analysis was performed by searching for relevant literature on PubMed, Scopus, and Web of Science databases. Eligibility included pre-post intervention studies using one way mobile messaging for health behaviour change. A random effects model was used for meta-analysis and standardised mean difference for effect size. Thereafter, a prospective, descriptive study was performed by administering an online health questionnaire to recruited WoW! members. Lastly, a quasi-experimental two-arm intervention was piloted on the participants recruited in the descriptive study. The intervention involved a WhatsApp bot that was programmed to send biweekly messages that were tailored to the intervention participants' pre-selected health goals and health barriers, using the COM-B model (Capability, Opportunity, Motivation Behaviour). The control condition included regular, non-tailored WhatsApp messages. After 12 weeks of messages, participants were prompted to complete a follow-up health assessment. Results: The systematic review and meta-analysis (n=43) found that unidirectional mobile messaging had minimal but significant effects on physical activity (d+: 0.14, 95% CI: 0.05 to 0.23, p=0.003, I2=65%), and no effect on weight loss (d+: 0.04, 95% CI: −0.02 to 0.10, p=0.21, I 2=29%). The descriptive study (n=95) observed a high prevalence of obesity (52%) and insufficient physical activity (70%) in the target population. The most frequently selected health goal by participants was to achieve a healthy weight (55%) which correlated to the high levels of obesity and physical inactivity. Upon the completion of the pilot intervention, only 26% of the 95 participants completed the follow-up post intervention. Although no significant changes were observed post intervention, most participants in the intervention group who completed the evaluation found the intervention acceptable. Discussion: The results of our systematic review and meta-analysis are similar to our findings in the feasibility pilot. In both, we showed that unidirectional, tailored mobile messaging had little to no effect on NCD risk factors, including physical activity and weight-related outcomes. These results suggest that messaging alone is not sufficient to elicit lifestyle changes to reduce the burden of NCDs and the associated risk factors. However, due to the small sample size, the study may have been underpowered to detect any significant changes. Future studies should consider using other intervention components, in addition to mobile messages, such as interactive texting, phone calls or in-person group sessions to potentially improve intervention effectiveness. Conclusion: Although mobile health has shown some potential in managing NCD risk factors, using unidirectional messaging alone may not be sufficient as a standalone intervention. More research using messaging in conjunction with other intervention components may be needed to realise the scalable potential of mHealth for NCD management in South Africa.